Digital Data Engagement and Health Behavior Diversity Among Smartwatch Users - Fang-Wu Tung; Liang-Ming Jia (World, 2026)
Smartwatches generate continuous personal health data, yet their value for self-care depends on users’ ability to engage with these data meaningfully. Using a cross-sectional survey of 838 adult smartwatch users in Taiwan, this study examined digital data engagement (DDE) as a data-specific construct linking smartwatch use to everyday self-care. DDE captured monitoring, interpretation, verification, and goal-oriented use of smartwatch-generated data, while health behavior diversity (HBD) represented the breadth of routine self-care practices across preventive, mind–body, physical activity/exercise, and restorative or expressive domains. The DDE-centered model showed that DDE was positively associated with health motivation, body awareness, and HBD. Health motivation showed the strongest association with HBD, whereas body awareness was not directly associated with HBD, suggesting that bodily cue awareness alone may not broaden self-care repertoires. HBD analysis further showed that smartwatch-enabled self-care was not merely exercise-oriented; preventive self-care had the highest item-adjusted coverage. Gender differences appeared mainly in domain composition, whereas health concern profiles were associated with both repertoire breadth and domain composition. These findings contribute a data-engagement perspective to smartwatch research and introduce HBD as a multidomain lens for evaluating everyday digital self-care beyond device access, tracking frequency, or single behavior change.